MPLS VPN Layer 3 Implementation and Comparative Analysis on Cisco and Huawei Devices Using GNS3 - Fadillah, Fauzan; Matheos Sarimolle, Frencis; Iskandar Mulyana, Dadang (International Journal of Science and Environment (IJSE), 2026)
This study discusses the implementation and comparative analysis of MPLS VPN Layer 3 on Cisco and Huawei devices using GNS3 simulation in an effort to understand the differences in performance and configuration characteristics of the two network vendors that are widely used in backbone infrastructure. The problem raised is how the configuration, routing stability, and performance of the MPLS VPN L3 service differ when running on devices with different architectures and operating systems. This study aims to provide a comprehensive overview of the structural and operational differences between Cisco IOS and Huawei VRP, including the OSPF routing process, MPLS label exchange, and the formation of VPNv4 BGP. The methods used include simulated topology design, device configuration, parameter testing such as latency, convergence time, throughput, and result analysis using a comparative approach. The results of the study are expected to be able to show the advantages and disadvantages of each vendor in the implementation of MPLS VPN L3 and provide a basis for consideration for practitioners or agencies in choosing network devices that suit operational needs. This research also contributes in the form of configuration documentation and performance analysis that can be a reference for the development of MPLS-based networks in academic and industrial environments.